When Science Meets Creativity: Elevating Microbiology Education With Art—Two Personal Experiences - Luis Andrés Yarzábal Rodríguez; Ramón Alberto Batista‐García (Microbial Biotechnology)
ABSTRACT Science communicators are more critical than ever in a time when misinformation and hoaxes dominate social media, especially during global emergencies like the COVID‐19 outbreak. Researchers are good at communicating with peers but often struggle to explain complex ideas to the public. As shown previously, expanding outreach by combining science and art is not only possible, but effective. In the case of microbiology, the synergy between these two apparently divorced areas can help educating our communities and raising microbiological awareness, especially among students. Since Alexander Fleming's pioneering attempts, microorganisms have fascinated artists. Art may help us demystifying microbes and making them more approachable, improving public involvement with science. This article presents two personal experiences using art to teach and communicate scientific ideas (mainly from the microbiology field) to our fellow citizens. Above all, we emphasise the importance of contributing to the scientific literacy of our societies at all ages—including underrepresented and disadvantaged groups—by exploring novel ways to address this gap. By doing so, we align with the concepts and aims of the International Microbiology Literacy Initiative (IMiLI).